Factors associated to usual physical activity in women - Oliveira,Paulo André Medeiros de (2015)
INTRODUCTION: attention has been focused on investigating the prevalence of physical activity PA in different populations.OBJECTIVE: to analyze factors associated with the usual practice of PA in women from areas of Santa Catarina, Brazil.METHODS: the cross-sectional study enrolled a sample of 2750 women with a mean age of 32.97±10.9 years. PA was assessed by the International Physical Activity Questionnaire IPAQ. The sample was divided into six groups: Southern Region; Itajaí Valley; Northern Region; Western Region; Highlands Region and the Greater Florianópolis Region, SC, Brazil. Statistical analysis was descriptive and inferential.RESULTS: approximately 68.3% of women were considered sufficiently active active + very active, in particular the Greater Florianópolis Region, SC, Brazil. In the practice of moderate and moderate + vigorous activity, the women of Western Region presented the highest averages 65±64 min/d; 105±102 min/d, respectively, and those in the range of 20-32 years old showed 61% chance of being considered active compared with women in the range of 46-59 years old. As for the body mass index BMI, women with normal weight of the South Region and Itajaí Valley regions had 2.24 95% CI;1.15-4.35 and 1.76 95% CI; 1.14-2.73 times more chances to be active when compared to the overweight women.CONCLUSION: women in the regions of Santa Catarina were considered sufficiently active. Moderate + vigorous PA was the most prevalent in the six regions studied.